In-sole plantar pressure device with optimization measurement techniques - O. Hussein; W.Z. Wan Hasan; A. Che Soh; H. Jafaar; H.R. Ramli; S.P. Ang; Zainidi Haji Abdul Hamid (Institute of Advanced Engineering and Science, 2020)
Doctors and clinicians rely on accurate underfoot pressure data to perform diagnosis of foot diseases. In sole pressure measurement systems are designed to provide such data but its implementation suffers from certain constraints such as the need for a spacer to be placed on the sensor when taking measurements and the need for multiple calibrations due to the fact that the sensor parameters tend to change without it. In this work, we proposed an optimization technique to address these limitations. The results obtained from testing indicate that the proposed device performed measurement of plantar pressure effectively. Also, the calculation of body weight using the proposed optimization technique is improved from 5.07% to 9.06%. For validation, the results are compared with the measurements from a commercial plantar pressure device (EMED system) as benchmark.